Green Extraction of Corn Silk Flavonoids Using NADES-UAE: Optimizing Conditions for Agricultural Waste Valorization - Anak Agung Sagung Intan Kwanira Gayatri; Anak Agung Gede Rai Yadnya Putra; Putu Oka Samirana (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Corn silk (of Zea mays L.) is an agricultural waste that has not been optimally utilized, even though it is known to contain flavonoid compounds with various pharmacological activities, such as antioxidant, anti-inflammatory, and antidiabetic effects. The flavonoid compounds in corn silk have the potential to be developed as natural raw materials for applications in the pharmaceutical and cosmetic fields. However, the extraction process for these active compounds often still uses organic solvents like methanol, which are toxic, flammable, and have negative impacts on health and the environment. Therefore, this study aimed to optimize the Ultrasound Assisted Extraction (UAE) method using a more environmentally friendly alternative solvent, namely Natural Deep Eutectic Solvent (NADES). The study was conducted in two main stages: selection of the best NADES composition and molar ratio from combinations of choline chloride with urea, glycerol, lactic acid, and malic acid; and optimization of UAE parameters including ultrasonic power, time, and temperature using the Response Surface Methodology (RSM) with the Box-Behnken Design (BBD) model. The determination of total flavonoid content was performed using the colorimetric method with AlCl? reagent and quercetin standard, and the measurements were taken using a UV-Vis spectrophotometer. The results showed that the NADES combination of choline chloride:urea (1:2) with the addition of 30% aquades produced the highest flavonoid content compared to 80% methanol solvent. The optimal conditions for UAE extraction were obtained at 100 % ultrasonic power, 30 minutes of extraction time, and a temperature of 70°C, resulting in a total flavonoid content yield of 96.02 ± 0.48 mgQE/g of corn silk powder. This study concluded that the combination of NADES and UAE method can significantly enhance the extraction yield of total flavonoids while also providing a more sustainable and environmentally friendly solution for the utilization of agricultural waste, such as corn silk.